Pengaruh Pendidikan Non-Formal dan Pelatihan Keterampilan Terhadap Kinerja Womenpreneur di Pedesaan Kabupaten Tasikmalaya - Ghaida Nur Azizah; Alfin Nur Arifah; Herdiyanti; Rina Madyasari (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2026)
Women entrepreneurs in rural areas occupy a pivotal position within Indonesia's inclusive economic development; however, the level of their business performance remains suboptimal due to constrained access to capacity-building initiatives. The objective of this study was to assess the extent to which non-formal education and skill development increase the welfare of female entrepreneurs in a rural district of Tasikmalaya Regency. Through a survey design and quantitative explanatory techniques, information was collected from 100 female micro-business owners selected through purposive sampling. The major data collection instrument was a structured questionnaire with a 1–5 Likert scale. Multiple linear regression was then utilized to examine the data with SPSS software. The outcomes showed that the performance of female entrepreneurs was positively and statistically significantly influenced by non-formal education and skills development. Taken together, these two variables account for 51.0% of the total variance in womenpreneur performance. These results carry important implications for policymakers and local government authorities, who are urged to institutionalize and integrate non-formal education and skills training into structured empowerment frameworks aimed at advancing business performance and economic self-reliance among rural women in Tasikmalaya Regency.